Dynamic behaviors in two-layer coupled oscillator system. (March 2021) - Yi, Wang; Yu, Xue; Xue, Wang; Bing-ling, Cen; Yan-feng, Qiao
Abstract: In this paper, we present a two-layer coupled oscillator model, in which the first layer is composed of the nearest neighbor coupled identical oscillator, the second layer is composed of the global coupled identical oscillator, and there is a one-way point-to-point drive from the second layer to the first layer. In this system, the driven layer changes from unsynchronized state to synchronized state with the change of parameters. During this transformation, we found the existence of chimer state. And the dynamic behavior of the system had been studied. The critical value for the state transition had been caught.